O diálogo e suas implicações na prática pedagógica - Barbosa, Regina Carla de Jesus (2018)
The objective of this research was to investigate the concept of dialogue and the pedagogical practice in the view of high school teachers of a federal public school and how the dialogue appears in the teaching practice in classroom. The theoretical basis is the assumptions of Martin Buber. It is a qualitative study, in which semi-structured interviews with Philosophy, Mathematics and Portuguese teachers, lesson observations from each of these disciplines and analyzing the documents of the General Teaching Plan (GTP) and the Didactic Sequence Plans (DSP) of the mentioned disciplines of the researched institution were used as an instrument for collecting and constructing the data. The collected data were analyzed in light of the theory of Content Analysis of Bardin (2011). Based on the raw results obtained and the inferences made on data, the following categories emerged: conception of dialogue, dialogue and pedagogical practice, presence of dialogue in conditions of the teaching-learning process. From the analysis, it was possible to verify that teachers have controversial opinions on the theme: most perceive the dialogue as interaction, a moment of listening and speaking, and a minority understands the dialogue as a simple exchange of information. All teachers, despite the differences in conceptual aspect, consider the dialogue important, fundamental in the teaching-learning process. The observations revealed that the teachers' speech and pedagogical doing are in line in terms of dialogue. Regarding the documents, it was verified that they favor a teaching method based on the student's knowledge, that valorizes their own reality, aiming at the formation of an autonomous and critical individual; in this way, a dialogical practice is implicitly favored.